THE SURVEYING OF THE POLARITY BY MOOD ADJUNCTS IN PERSIAN LANGUAGE BASED ON FUNCTIONAL GRAMMAR APPROACH - Pahlavan nezhad, Mohammad Reza; Tavakoli, Farzaneh Hassanzadeh (European Scientific Journal, ESJ, 2013)
Polarity determines whether the message is positive or negative. This key element of every context can be expressed through mood adjuncts. The present study aimed at surviving the polarity of Persian mood adjuncts based on functional grammar approach. Both positive and negative discourses were presented and discussed. To achieve the purpose of the study, however, some negative mood adjuncts such as "hargez"(never), "be zahmat"(scarcely), "be nodrat"(rarely), and some positive mood adjuncts including "hamishe"(always), "aqlab" (often), "mamulan" (usually) and "barxi auqat" (sometimes) were discussed. Finally it was found that to carry a severe negative message in contexts using the negative polarity mood adjuncts in Persian language ٫"negative" markers are required